Phubbing in Social Interaction: A Phenomenological Study on the Urban Young Generation in Pontianak - Zulkarnain; Muhammad Sadikin; Auliya Rochman (Universitas Muhammadiyah Palu, 2025)
The rapid advancement of digital technology has significantly changed the pattern of social interaction, especially among urban youth. One form of this transformation is